PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP PEMENUHAN KEBUTUHAN INFORMASI MAGANG DAN STUDI INDEPENDEN BERSERTIFIKAT (MSIB) PADA KALANGAN MAHASISWA - Chika Marsanda, (2023)
Instagram is a well-liked form of media in Indonesia, and Ditjen Dikti turned the Instagram account @Magangmerdeka into a source of information in order to satisfy students' demands for information on MSIB, the program with the highest number of supporters but few reliable information sources. This study was done to find out how much of an impact students who follow the @Magangmerdeka Instagram account have on meeting the information demands of MSIB. The Uses and Gratification theory serves as the basis for this investigation. Explanatory quantitative methodology was employed in this study. Instagram users that follow the @Magangmerdeka account make up the population of this study. 100 samples were collected using a purposive sampling technique. Inferential statistical test analysis, including correlation, regression, coefficient of determination, and hypothesis testing, is used in this work. The findings demonstrated that using social media significantly affects meeting information demands, and there is a strong association between the factors.